2012
DOI: 10.5194/hess-16-3061-2012
|View full text |Cite
|
Sign up to set email alerts
|

Combining ground-based and airborne EM through Artificial Neural Networks for modelling glacial till under saline groundwater conditions

Abstract: Abstract. Airborne electromagnetic (AEM) methods supply data over large areas in a cost-effective way. We used Artificial Neural Networks (ANN) to classify the geophysical signal into a meaningful geological parameter. By using examples of known relations between ground-based geophysical data (in this case electrical conductivity, EC, from electrical cone penetration tests) and geological parameters (presence of glacial till), we extracted learning rules that could be applied to map the presence of a glacial t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 32 publications
(23 reference statements)
0
44
0
1
Order By: Relevance
“…Studies with related combinations of methods are shown, e.g. by Jørgensen et al (2012), Bosch et al (2009), Rumpel et al (2009), Sulzbacher et al (2012) and Gunnink et al (2012).…”
Section: T Burschil Et Al: Compiling Geophysical and Geological Infmentioning
confidence: 99%
“…Studies with related combinations of methods are shown, e.g. by Jørgensen et al (2012), Bosch et al (2009), Rumpel et al (2009), Sulzbacher et al (2012) and Gunnink et al (2012).…”
Section: T Burschil Et Al: Compiling Geophysical and Geological Infmentioning
confidence: 99%
“…Other automatic methods of integrating AEM data into geological models are geostatistical methods presented by, for example, Gunnink et al (2012), using artificial neural networks, or He et al (2014), using transition probabilities.…”
Section: Advantages and Limitationsmentioning
confidence: 99%
“…However, it is common to measure the attitude variations of ATEM systems directly or indirectly by installing an inertial navigation system or two laser altimeters, differential Global Position System (GPS) devices and inclinometers (Gunnink et al, 2012;Hefford et al, 2006;Smith, 2001), and then we can use the Neumann mutual inductance formula and the measured attitude variations to transform the coordinates of circular coils or polygonal coils at arbitrary attitudes with a rotation matrix. Thus the singular values of two vertical coils can be calculated as well as the mutual inductance of polygonal and circular coils at arbitrary attitudes and arbitrary positions.…”
Section: Introductionmentioning
confidence: 99%